Obstructive jaundice caused by a biliary mucinous cystadenoma in a woman: a case report - Chandrasinghe, Pramodh C (BioMed Central, 2013)
INTRODUCTION: Mucinous cystadenoma of the liver is a rare (less than 5%) neoplasm. This condition is more common in young women and accounts for non-specific symptoms. Cyst adenomas commonly affect the intrahepatic system (90%) and are rarely found in the extrahepatic biliary system or affecting both the systems. CASE PRESENTATION: A 39-year-old Sinhalese woman presented with features of obstructive jaundice and was found to have a biliary neoplasm on imaging. In the absence of a definitive diagnosis despite extensive imaging she underwent preoperative endoscopic biliary drainage followed by a left hemihepatectomy with Roux-en-Y hepaticojejunostomy. A pathological examination of the specimen revealed an obstruction of the bile duct caused by a biliary mucinous cystadenoma affecting both the intrahepatic and extrahepatic systems. CONCLUSIONS: Biliary mucinous cystadenoma rarely present with obstructive jaundice affecting both intrahepatic and extrahepatic ducts. Exhaustive investigation might not help in the diagnosis and may need to be treated based on clinical judgment. The definitive treatment modality is surgery due to its malignant potential. The operative procedure is technically demanding and is best performed at specialist centers to minimize complications.